Effectiveness of the Combination of Realistic Mathematics Education and Quantum Learning Approaches in Learning Mathematics Class VII SMP Negeri 2 Larompong - Muhammad Darwis M; Adea Nurjuwita; Ilham Minggi (Issues in Mathematics Education (IMED), 2025)
Abstract. The research is a pre-experiment study that aims to determine the Effectiveness of the Application of the Combination of Realistic Mathematics Education and Quantum Learning Approaches in Learning Mathematics Class VII SMP Negeri 2 Larompong. This research was conducted in January 2023 and the subject was Class VII 1 SMP Negeri 2 Larompong consisting of 18 students. The research data were obtained through the learning implementation observation sheet, student activity observation sheet, student learning outcomes test (pretest) and after (posttest) the implementation of the action, and student interest in learning mathematics questionnaire. The data were analyzed quantitatively by using descriptive statistical analysis and inferential statistical analysis. The results are (1) The average student mathematics learning outcomes was 84,89, higher than the KKM (75); (2) The increase in student learning outcomes is 0,7976 or in the high category; (3) Student activity in the learning process during the 4 meetings was 93% or in the active category; (4) The increase in students interest in learning mathematics descriptively is 0,6313 and there are 77.78% with a normalized gain value of more than 0,3 or in the moderate category.